Drastic Change in Technical Education in India - Sawhney, Arun Chnadra (PREPARE@u® | IEI Conferences, 2021)
The formal education focuses on the too much theory and fundamental concepts in different subjects and does neither inculcate any kind of entrepreneurship skills to prepare them to set up their own industries nor prepare them with practical skills to make them directly employable in any manufacturing, construction or service industry. This calls for urgent need for bringing drastic changes in technical education to bridge the gap that existing between the needs of the industry and the academic curricula.